2003
DOI: 10.1093/nar/gkg786
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel splice forms and functional analysis of cancer-specific alternative splicing in human expressed sequences

Abstract: We report here a genome-wide analysis of alternative splicing in 2 million human expressed sequence tags (ESTs), to identify splice forms that are upregulated in tumors relative to normal tissues. We found strong evidence (P < 0.01) of cancer-speci®c splice variants in 316 human genes. In total, 78% of the cancer-speci®c splice forms we detected are con®rmed by human-curated mRNA sequences, indicating that our results are not due to random mis-splicing in tumors; 73% of the genes showed the same cancer-speci®c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 30 publications
2
144
0
3
Order By: Relevance
“…It is known that splicing defects play a role in many human diseases, 50,51 including numerous types of cancer. [52][53][54][55] Similarly, APA has a demonstrated regulatory role in human disease. 30,[56][57][58][59] Thus, coordinated APA and upstream AS could generate alternatively spliced mRNA isoforms with unique 3 0 UTRs that dictate mRNA half-lives and protein product functions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that splicing defects play a role in many human diseases, 50,51 including numerous types of cancer. [52][53][54][55] Similarly, APA has a demonstrated regulatory role in human disease. 30,[56][57][58][59] Thus, coordinated APA and upstream AS could generate alternatively spliced mRNA isoforms with unique 3 0 UTRs that dictate mRNA half-lives and protein product functions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 10 -30% of alternatively spliced human genes have tissue-specific variants (Xu et al, 2002), whereas 316 genes have been shown to have cancer-specific variants (Xu and Lee, 2003). Production of alternative transcripts may be a consequence of disease such as cancer (Mercatante and Kole, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence suggests that altered splicing is associated with and possibly involved in tumor progression and/or metastasis (Venables, 2004). Recent computational analyses, based on alignments of expressed sequence tags to human RefSeq mRNAs or human genomic DNA, revealed that many alternatively spliced variants were significantly associated with cancer, and the majority of these genes have functions related to cancer (Wang et al, 2003;Xu and Lee, 2003). In general, the direct causes behind the alteration of pre-mRNA splicing can be divided into two categories: mutations in cis-elements and changes in trans-acting factors.…”
Section: Ptb In Ovarian Cancer X He Et Almentioning
confidence: 99%